2016
DOI: 10.1089/jpm.2015.0276
|View full text |Cite
|
Sign up to set email alerts
|

Association between Daytime Activity, Fatigue, Sleep, Anxiety, Depression, and Symptom Burden in Advanced Cancer Patients: A Preliminary Report

Abstract: Background: There is limited research in advanced cancer patients (ACP) regarding association between objectively measured daytime activity and sleep (as measured by actigraphy), patient characteristics, and cancer symptoms (fatigue, sleep, anxiety, depression, cachexia, and symptom distress scores [SDSs]). Objectives: Our aim of the study was to determine the association between mean daytime activity (MDTA) and the following items: fatigue (FACIT-F), SDSs (Edmonton Symptom Assessment Scale [ESAS]), sleep qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0
10

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 56 publications
8
28
0
10
Order By: Relevance
“…27,58,69e71 Prior studies also found that anxiety, depression, and pain was associated with disturbance in sleep. 72,73 In our study, we also found improvement of PSQI total sleep score by two points, P ¼ 0.055 (which is better than most pharmacological trials). We also found significant improvement of PSQI daytime dysfunction, sedative medication use, anxiety, depression, and pain scores.…”
Section: Discussionsupporting
confidence: 68%
“…27,58,69e71 Prior studies also found that anxiety, depression, and pain was associated with disturbance in sleep. 72,73 In our study, we also found improvement of PSQI total sleep score by two points, P ¼ 0.055 (which is better than most pharmacological trials). We also found significant improvement of PSQI daytime dysfunction, sedative medication use, anxiety, depression, and pain scores.…”
Section: Discussionsupporting
confidence: 68%
“…Two independent datasets were used to test this hypothesis. Based on the convenience of its noninvasive methodology and previous reports in smaller cohorts showing an association with fatigue and sleep problems, [19][20][21][22][23][24][25] we selected the circadian rest-activity rhythm as measured by wrist actigraphy. 26,27 Wrist actigraphy has been validated as an objective biomarker of circadian function.…”
Section: Introductionmentioning
confidence: 99%
“…If the treatment is only symptomatic and ignores the patient's psychological needs, it may aggravate the condition and seriously affect the quality of life and survival of the patient [8]. Therefore, good communication between doctors and patients can ease the patient's anxiety, make the patient treat the disease more actively, and improve the quality of life of patients with advanced cancer [9][10].…”
Section: Discussionmentioning
confidence: 99%